Design Thinking as a Business Model for Empowering Creative Entrepreneurs in the Digital Era - Abbas, Diego; Siahaan, Kelvin; Yusup, Muhamad (Pandawan Sejahtera Indonesia, 2025)
In the rapidly evolving digital economy, creativepreneurs individuals who transform artistic and creative ideas into marketable ventures face unique challenges in sustaining innovation, meeting user needs, and creating scalable value. Traditional business models often fall short in supporting the fluid, iterative, and user centric nature of creative industries. This study explores the integration of design thinking as a strategic business model to empower creativepreneurs in the digital era. The research aims to investigate how the principles of empathy, ideation, prototyping, and testing within design thinking can foster innovation, user engagement, and business growth among creative driven entrepreneurs. A qualitative research methodology was adopted, employing in-depth interviews and case studies involving 25 selected creativepreneurs from various digital based industries, such as digital art, fashion, content creation, and digital product design. Data were analyzed using thematic analysis to identify common patterns and insights. The findings indicate that the application of design thinking significantly enhances creativepreneurs ability to identify user pain points, develop user centered solutions, and adapt quickly to market feedback. Moreover, design thinking promotes continuous innovation and resilience, two critical traits for success in the digital landscape. In conclusion, design thinking is not only a creative problem solving tool but also a robust business model that aligns with the values and needs of modern creativepreneurs. The study recommends incorporating design thinking frameworks into entrepreneurship education and incubator programs to support creative economy growth in the digital age.